The Improvement Genetic Quality Of Muscovy Ducks: Review - Fitasari, Eka; Santoso, Erik Priyo; Sumiati, Astri (Universitas Halu Oleo, 2022)
Indonesia has the potential of muscovy duck resources with various characteristics and qualities that are spread throughout the region. muscovy duck has a larger body size than ducks but has a weakness in terms of lower egg production. To produce ducks with high body weight and egg production, Indonesian breeders often cross muscovy ducks with ducks. The use of a cross model with 4-crossbreeding is an efficient strategy, but genetic improvements need to be made to the two parents including the muscovy duck and the ducks itself because, in some crosses, sterile hybrid results will be obtained. The use of artificial insemination can be done to support the crossing of offspring in obtaining the desired production results. Therefore, a recording should be made to determine the quality of the offspring either using natural marriage or with the help of artificial insemination and its effectiveness on fertility in the next few periods. The use of marker-assisted selection (MAS) can help in the selection to get superior mutton traits and to find out the metabolic pathways related to the formation of the desired body weight and liver weight.Keywords: genetic quality, 4-crossbreeding, muscovy duck, marker-assisted selection (MAS)